Kelayakan Kekayaan Intelektual Sebagai Agunan Pembiayaan - Nurhidayati, Nurhidayati; Sugiyah, Sugiyah; Yuliantari, Kartika (Widya Cipta: Jurnal Sekretari dan Manajemen, 2023)
Creative economic growth as the basis for national economic growth must be supported by various parties. Intellectual property as a result of creative economic actors needs to be developed through added value in order to provide greater economic benefits. The government has issued regulations on the creative economy and its implementing regulations. The hope is that it will provide a strong foundation for the parties to support the development of the creative economy. The purpose of this study was to determine the feasibility of financing the creative economy with intellectual property guarantees. This research is a qualitative descriptive study using a normative juridical method by examining several legal rules that support the theme of this research. The results of the study show that intellectual property as a source of income for creative economy actors, in its implementation is still not optimal to be used as collateral for bank and non-bank financial institutions, in order to help finance the creative economy. The main obstacle is related to the issue of valuation of intellectual property rights, where it is still necessary to have several parties who have the competence to carry out the valuation. The community does not yet have an adequate understanding of intellectual property as collateral for credit/financing, therefore a continuous education program is needed in the future..